Regulation of I kappa B alpha and p105 in monocytes and macrophages persistently infected with human immunodeficiency virus. - McElhinny, J A (1995)
The mechanisms regulating human immunodeficiency virus (HIV) persistence in human monocytes/macrophages are partially understood. Persistent HIV infection of U937 monocytic cells results in NF-kappa B activation. Whether virus-induced NF-kappa B activation is a mechanism that favors continuous viral replication in macrophages remains unknown. To further delineate the molecular mechanisms involved in the activation of NF-kappa B in HIV-infected monocytes and macrophages, we have focused on the regulation of the I kappa B molecules. First, we show that persistent HIV infection results in the activation of NF-kappa B not only in monocytic cells but also in macrophages. In HIV-infected cells, I kappa B alpha protein levels are decreased secondary to enhanced protein degradation. This parallels the increased I kappa B alpha synthesis secondary to increased I kappa B alpha gene transcription, i.e., increased RNA and transcriptional activity of its promoter-enhancer. Another protein with I kappa B function, p105, is also modified in HIV-infected cells: p105 and p50 steady-state protein levels are increased as a result of increased synthesis and proteolytic processing of p105. Transcriptional activity of p105 is also increased in infected cells and is also mediated by NF-kappa B through a specific kappa B motif. These results demonstrate the existence of a triple autoregulatory loop in monocytes and macrophages involving HIV, p105 and p50, and MAD3, with the end result of persistent NF-kappa B activation and viral persistence. Furthermore, persistent HIV infection of monocytes and macrophages provides a useful model with which to study concomitant modifications of different I kappa B molecules.